Limitations for current production in Geobacter sulfurreducens biofilms - Bonanni, Pablo Sebastian (2013)
Devices that exploit electricity produced by electroactive bacteria such as Geobacter sulfurreducens have not yet been demonstrated beyond the laboratory scale. The current densities are far from the maximum that the bacteria can produce because fundamental properties such as the mechanism of extracellular electron transport and factors limiting cell respiration remain unclear. In this work, a strategy for the investigation of electroactive biofilms is presented. Numerical modeling of the response of G. sulfurreducens biofilms cultured on a rotating disk electrode has allowed for the discrimination of different limiting steps in the process of current production within a biofilm. The model outputs reveal that extracellular electron transport limits the respiration rate of the cells furthest from the electrode to the extent that cell division is not possible. The mathematical model also demonstrates that recent findings such as the existence of a redox gradient in actively respiring biofilms can be explained by an electron hopping mechanism but not when considering metallic-like conductivities.